Impacto estratégico del proteccionismo implementado por Brasil y Argentina en el ámbito de la industria automotriz mexicana (Strategic impact of protectionism implemented by Brazil and Argentina within the scope of the Mexican automotive industry) - García Pérez, María Laura; Vargas Hernández, José G. (Facultad de Contaduría Pública y Administración U.A.N.L., 2013)
Abstract. Today protectionist actions have been highly adopted by the nations, that in order to cope with the constant crises that threaten to slow economic growth. The cancellation of trade agreements has led to a strategic management restructuring, which now seeks to minimize the negative effects. Mexico is not the exception, because last year suffered the imposition of a series of protectionist guidelines by Brazil and Argentina, which were intended to reduce the number of exports that are made to these South American economies. This study intends to analyze the impact and strategic changes adopted by Mexico in the automotive industry as a result of these regulations. Using a method of analysis of quantitative and qualitative data is to estimate the damages to the sector as well as the measures taken by Mexico to decrease side effects.